The use of materials of Kazakh ethnopedagogy in the studyof the subject “natural science” in primary school (Gumilyov Journal of Pedagogy, 2025)
This article comprehensively examines the role and influence of centuries-old educational experience within the traditional pedagogical culture of the Kazakh people. It considers this as an integral part of universal values in the development of intellectual abilities among the modern young generation. The article discusses the deliberate and effective use of Kazakh ethnopedagogy materials in the educational activities of students in special primary classes.In the context of the open development of modern global society, we emphasize the importance and scientific significance of improving education content to address the challenges of holistic education and the cultivation of national values in children. From the authors' perspective, there is a need to focus on the deliberate and systematic utilization of Kazakh ethnopedagogy materials in shaping the value orientations of younger schoolchildren during the teaching of the “natural science” subject in primary classes. These classes lay a solid foundation for education and development.Within the scope of this research, the article demonstrates and formulates the possibility for primary school students to achieve a deep understanding of the “natural science” subject by effectively utilizing materials from Kazakh ethnopedagogy. This approach relies not only on the advanced experience of educating generations, which has withstood centuries of scrutiny but also on the spiritual heritage of prominent historical figures in Kazakh pedagogical science. The article provides concreteexamples from the deliberate, systematic, and rational use of Kazakh ethnopedagogy materials in the in-depth explanation and mastery of complex topics, concepts, and phenomena that underpin the field of “natural science”.